How do macroeconomics’ students assess the use of digital learning resources? A post-pandemic analysis. - Expósito-García, Alfonso; Pablo-Romero, María; Sánchez-Rivas, Javier (My University, 2024)
This study analyses student assessment outcomes on three types of Digital Learning Resources created for online teaching of Macroeconomics during the Covid-19 pandemic: digital teaching notes, digital PowerPoint presentations and short videos of complex graphics. Results indicate that all Digital Learning Resources offered to the students are positively assessed in terms of quality, use intensity, utility and general assessment. Digital notes are significantly the most highly rated, which seems to indicate a preference for traditional learning resources. Additionally, our analysis shows that the intensity of Internet use and study time constitute significant factors in explaining the students' higher perception of the teaching notes, compared to the other learning resources. Student gender is not a significant factor to explain the students’ assessments.
Keywords: Macroeconomía - Estudio y enseñanza superior; Tecnología educativa; Macroeconomics; Students; Pandemics; Digital learning resources